A publicidade em outdoor nas ruas de Vitória : a cidade como espaço de educação - Souza, Flávia Mayer dos Santos (2015)
It searches to analize, from the billboards study run on two avenues in the city of Vitoria, narratives that circulate more intensely in contemporary society and thus educate society. Seeks to understand also the relationships established between the subjects and the billboard advertising, intending then check whether and how advertising affects the subject, whether and how educates the subject and the uses that people who circulate in the studied space make it. The theoretical framework includes discussions on consumption, from Bauman (2001, 2008), Certeau (1999), among other authors; is dedicated to the debate about advertising in billboard having supported the studies of Pinheiro and Sabadin (1990); discusses the semiotic theory, recovering the concept developed by Fiorin (2011), Barros (2010) and especially by Landowski (2002, 2004), a researcher who has also contributed to reflection on the possibility of analysis by means of chaining advertising, forming thus a sequence. Finally, the debate on the sensitive education is sustained, especially in Greimas (2002). This is a descriptive and explanatory study that combines both documentary analysis and field research. The documents in question are the ads in billboard, recorded through photography, monthly, between July 2012 and January 2014. The field research turns to talk with those who make use of at least one way and, therefore, is intended to understand the relationships established between the subjects and the billboards.